Toleranzdiskurse in der Frühen Neuzeit - Vollhardt, Friedrich; Bach, Oliver; Multhammer, Michael (Frühe Neuzeit, 2015)
Until quite recently, it was unthinkable that conflicts would arise in the Western world that recalled religious wars of the distant past. It may be questionable whether recalling the historical origins of our notion of tolerance will change today's conflicts, yet it is important to understand the past, as potential solutions may be found in the early modern discourse on the politics of natural rights. This volume offers the necessary foundation --
Literaturangaben
Keywords: Geschichte 1550-1763; Konferenzschrift -- 2013 -- München; Geschichte 1500-1800; Religiöser Pluralismus; Häresie; Religiöse Toleranz; Politische Philosophie; Pluralismus; Toleranz